2021
DOI: 10.3390/sports9100141
|View full text |Cite
|
Sign up to set email alerts
|

Sprinting Biomechanics and Hamstring Injuries: Is There a Link? A Literature Review

Abstract: Hamstring strain injury (HSI) is a common and costly injury in many sports such as the various professional football codes. Most HSIs have been reported to occur during high intensity sprinting actions. This observation has led to the suggestion that a link between sprinting biomechanics and HSIs may exist. The aim of this literature review was to evaluate the available scientific evidence underpinning the potential link between sprinting biomechanics and HSIs. A structured search of the literature was complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Although more typical for team sports and related to sprinting [ 132 , 133 ], hamstring injuries also occur in distance runners [ 28 ]. The risk of hamstring injury can be reduced by flexibility training as well as strength training, as Wan et al [ 134 ] found that mobility training statistically significantly lengthened the semimembranosus and long head of the biceps femoris ( p ≤ 0.026) and reduced the maximum load on the hamstrings, while strength training increased the length and reduced maximum load on all hamstring muscles.…”
Section: Resistance Exercise For Reducing the Risk Of Running-related...mentioning
confidence: 99%
“…Although more typical for team sports and related to sprinting [ 132 , 133 ], hamstring injuries also occur in distance runners [ 28 ]. The risk of hamstring injury can be reduced by flexibility training as well as strength training, as Wan et al [ 134 ] found that mobility training statistically significantly lengthened the semimembranosus and long head of the biceps femoris ( p ≤ 0.026) and reduced the maximum load on the hamstrings, while strength training increased the length and reduced maximum load on all hamstring muscles.…”
Section: Resistance Exercise For Reducing the Risk Of Running-related...mentioning
confidence: 99%
“…The two cases of action mentioned above, such as significantly greater anterior pelvic tilt or thoracic lateral flexion, both contain the sudden appearance or persistence of mis-takes or abnormalities in action, and were deemed as an irrefutable factor contributing to the injury and re-injury [81][82][83]. However, this viewpoint is subject to be supported by experimental evidence.…”
Section: Possible Performance Of Motor Control During Hamstrings Acut...mentioning
confidence: 99%
“…Ekstrand et al [ 2 ] proposed that the increase of intensity that elite men’s football has experimented with in the last years, with a larger volume of high-intensity actions and a congested competitive calendar, is a potential explanation for the high hamstring injury incidence. Hence, there is still much to understand about the causes of hamstring muscle injury, particularly about the influence of sprinting biomechanics and the effect of running exposure before the injury occurs during a match [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%